818 Association Between Intraoperative LFP, Lead Location, and Outcomes in Subthalamic Nucleus Deep Brain Stimulation for Parkinson's Disease. (1st April 2022) - Katlowitz, Kalman; Ince, Nuri Firat; Tarakad, Arjun; Sheth, Sameer A.; Viswanathan, Ashwin
Abstract : INTRODUCTION: Imaging-based, LFP-based and empirical programming strategies can be used to determine the optimal therapeutic contact for deep brain stimulation, but the most efficient strategy is unclear. METHODS: In this prospective, IRB-approved study, 10 awake patients were implanted with bilateral STN DBS using both an electrophysiologically- and imaged-confirmed technique. Once the DBS lead had been secured, LFP signals were recorded with a Grapevine Neural Amplifier (Ripple Neuro, UT) at 30 KHz and 16-bit A/D resolution, and LFPs were down-sampled to 2 KHz before further processing. Stereotactic CTs acquired two weeks postoperatively were fused to the pre-operative 3T, T2 weighted MRI and processed using the SureTune platform (Medtronic, MN). Therapeutic DBS programming parameters were obtained 6 months post-implantation, along with pre- and post-operative UPDRS Part III scores. RESULTS: There was a 54% reduction in the UPDRS score when comparing the preoperative OFF score, to the 6 month postoperative OFF Meds/ON Stimulation Score. 50% of the chosen contacts were in the STN only, 10% in the ZI only, and 35% in both. One lead was found to be outside the segmented STN and ZI; this patient did not experience clinical improvement based on their Part III UPDRS score. Beta (8-30Hz) power was 4.1 times higher for electrodes within the STN versus out, 1.4 times for ZI versus out, and 5.9 times higher for both versus neither. The average beta power was 15% higher in the chosen therapeutic contacts over those contacts not used. Lastly, we found that the number of electrodes within the STN correlated with the decrease in the UPDRS score (r=0.27). CONCLUSIONS: There is a strong correlation between image-based electrode localization, LFP characteristics, and clinical outcomes in patients undergoing STN DBS for Parkinson Disease. Focused programming strategies based on either imaging or LFP data can facilitate identification of the optimal therapeutic contact.